Analisis Kemampuan Literasi Matematika dalam Materi Transformasi Dilatasi Kelas XI D SMPN 4 Sungai Penuh - Hanifa Faradilla; Thessa OKtavia; Putri Yulia (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2025)
The advancement of knowledge closely linked to technological progress imposes a demand on countries to enhance the quality of their human resources (HR). In Indonesia, as a developing nation, the abundance of human resources requires an elevation in quality to remain competitive on a global scale. Improving the national education quality, particularly in mathematics, emerges as a strategic step in nurturing a competitive HR. Mathematics plays a pivotal role in equipping students with logical, analytical, and creative thinking skills, as well as collaborative abilities. However, the results of the 2018 PISA survey indicate a low level of mathematical literacy in Indonesia. Factors such as students' weak mathematical reasoning, insufficient practice in problem-solving, and a mismatch between test materials and the curriculum are major contributors to the poor performance in mathematical literacy. The significance of mathematical literacy is reflected in five competencies that students should possess, all of which support mathematical literacy. Mathematical literacy functions in applying mathematical knowledge in the context of everyday life, aligning with the demands of an ever-evolving era. To achieve the goal of mathematics education that aligns with the demands of mathematical literacy, attention is required towards content, processes, and context in mathematics learning. Hence, efforts to enhance the quality of mathematics education in Indonesia should consider these aspects to foster competent students capable of facing the challenges of the modern world.